Enzymatic Strategies to Detoxify Gluten: Implications for Celiac Disease. (20th September 2010) - Caputo, Ivana; Lepretti, Marilena; Martucciello, Stefania; Esposito, Carla
Abstract : Celiac disease is a permanent intolerance to the gliadin fraction of wheat gluten and to similar barley and rye proteins that occurs in genetically susceptible subjects. After ingestion, degraded gluten proteins reach the small intestine and trigger an inappropriate T cell-mediated immune response, which can result in intestinal mucosal inflammation and extraintestinal manifestations. To date, no pharmacological treatment is available to gluten-intolerant patients, and a strict, life-long gluten-free diet is the only safe and efficient treatment available. Inevitably, this may produce considerable psychological, emotional, and economic stress. Therefore, the scientific community is very interested in establishing alternative or adjunctive treatments. Attractive and novel forms of therapy include strategies to eliminate detrimental gluten peptides from the celiac diet so that the immunogenic effect of the gluten epitopes can be neutralized, as well as strategies to block the gluten-induced inflammatory response. In the present paper, we review recent developments in the use of enzymes as additives or as processing aids in the food biotechnology industry to detoxify gluten.